2006
DOI: 10.1118/1.2241278
|View full text |Cite
|
Sign up to set email alerts
|

SU‐FF‐T‐357: Physical and Biological Characteristics of Megavoltage Grid Radiation Therapy

Abstract: Purpose: Dosimetric characteristics of a newly designed GRID block for megavoltage radiotherapy were investigated using TLD, film, and ionization chamber. Therapeutic advantage of this treatment modality was determined using a linear quadratic model in terms of treatment dose, GRID hole size, center‐to‐center spacing between the holes, and sensitivity of tissues to radiation. Method and Materials: Recently a newly redesigned GRID block has been introduced by Radiation Product Design, Inc. for different linear … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…TR was evaluated with increases in prescription doses of 10, 15, and 20 Gy. In a dosimetric study on grid therapy by Dou et al [21], similar gain was determined for a single fraction dose up to 30 Gy. In a clinical evaluation of grid therapy patients, Mohiuddin et al [22] showed that doses of 15-20 Gy achieved a 100% palliative response versus 79% for less than 15 Gy.…”
Section: Discussionmentioning
confidence: 99%
“…TR was evaluated with increases in prescription doses of 10, 15, and 20 Gy. In a dosimetric study on grid therapy by Dou et al [21], similar gain was determined for a single fraction dose up to 30 Gy. In a clinical evaluation of grid therapy patients, Mohiuddin et al [22] showed that doses of 15-20 Gy achieved a 100% palliative response versus 79% for less than 15 Gy.…”
Section: Discussionmentioning
confidence: 99%